Full-Length Transcriptome Sequencing Reveals Tissue-Specific Gene Expression Profile of Mangrove Clam Geloina erosa - Liao, Xin; Liu, Yunqing; Han, Tingyu; Yang, Mingliu; Liu, Wenai; Wang, Yadi; He, Chunpeng; Lu, Zuhong (Frontiers in Physiology, 2022)
Mollusca is the second largest animal phylum and represents one of the most evolutionarily successful animal groups. Geloina erosa, a species of Corbiculidae, plays an important role in mangrove ecology. It is highly adaptable and can withstand environmental pollution and microbial infections. However, there is no reference genome or full-length transcriptome available for G. erosa. This impedes the study of the biological functions of its different tissues because transcriptome research requires reference genome or full-length transcriptome as a reference to improve accuracy. In this study, we applied a combination of Illumina and PacBio single-molecule real-time sequencing technologies to sequence the full-length transcriptomes of G. erosa tissues. Transcriptomes of nine samples obtained from three tissues (hepatopancreas, gill, and muscle) were sequenced using Illumina. Furthermore, we obtained 87,310 full-length reads non-chimeric sequences. After removing redundancy, 22,749 transcripts were obtained. The average Q score of 30 was 94.48%. In total, 271 alternative splicing events were predicted. There were 14,496 complete regions and 3,870 lncRNAs. Differential expression analysis revealed tissue-specific physiological functions. The gills mainly express functions related to filtration, metabolism, identifying pathogens and activating immunity, and neural activity. The hepatopancreas is the main tissue related to metabolism, it also involved in the immune response. The muscle mainly express functions related to muscle movement and control, it contains more energy metabolites that gill and hepatopancreas. Our research provides an important reference for studying the gene expression of G. erosa under various environmental stresses. Moreover, we present a reliable sequence that will provide an excellent foundation for further research on G. erosa.